Deletion of Trace Amine-Associated Receptor 1 Attenuates Behavioral Responses to Caffeine - Schwartz, Michael D.; Palmerston, Jeremiah B.; Lee, Diana L.; Hoener, Marius C.; Kilduff, Thomas S. (Frontiers in Pharmacology, 2018)
Trace amines (TAs), endogenous amino acid metabolites that are structurally similar to the biogenic amines, are endogenous ligands for trace amine-associated receptor 1 (TAAR1), a GPCR that modulates dopaminergic, serotonergic, and glutamatergic activity. Selective TAAR1 full and partial agonists exhibit similar pro-cognitive, antidepressant- and antipsychotic-like properties in rodents and non-human primates, suggesting TAAR1 as a novel target for the treatment of neurological and psychiatric disorders. We previously reported that TAAR1 partial agonists are wake-promoting in rats and mice, and that TAAR1 knockout (KO) and overexpressing mice exhibit altered sleep-wake and EEG spectral composition. Here, we report that locomotor and EEG spectral responses to the psychostimulants modafinil and caffeine are attenuated in TAAR1 KO mice. TAAR1 KO mice and WT littermates were instrumented for EEG and EMG recording and implanted with telemetry transmitters for monitoring locomotor activity (LMA) and core body temperature (Tb). Following recovery, mice were administered modafinil (25, 50, 100 mg/kg), caffeine (2.5, 10, 20 mg/kg) or vehicle p.o. at ZT6 in balanced order. In WT mice, both modafinil and caffeine dose-dependently increased LMA for up to 6 h following dosing, whereas only the highest dose of each drug increased LMA in KO mice, and did so for less time after dosing. This effect was particularly pronounced following caffeine, such that total LMA response was significantly attenuated in KO mice compared to WT at all doses of caffeine and did not differ from Vehicle treatment. Tb increased comparably in both genotypes in a dose-dependent manner. TAAR1 deletion was associated with reduced wake consolidation following both drugs, but total time in wakefulness did not differ between KO and WT mice. Furthermore, gamma band EEG activity following both modafinil and caffeine treatment was attenuated in TAAR1 KO compared to WT mice. Our results show that TAAR1 is a critical component of the behavioral and cortical arousal associated with two widely-used psychostimulants with very different mechanisms of action. Together with our previous findings, these data suggest that TAAR1 is a previously-unrecognized component of an endogenous wake-modulating system.